2020
DOI: 10.1017/s003118202000178x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and molecular detection of Trypanosoma spp. in cattle, goats and sheep in Somalia

Abstract: African animal trypanosomiasis (AAT) affects the livestock of 12.3 million Somalis and constrains their development and wellbeing. There is missing data on AAT in the country after the civil war of the 1990s. Therefore, this study has aimed to assess the prevalence of Trypanosoma spp. in 614 blood samples from cattle (n = 202), goats (n = 206) and sheep (n = 206) in Afgoye and Jowhar districts, Somalia using parasitological and molecular methods. Twenty-one out of 614 (3.4%; 95% CI: 2.1–5.2%) and 101/614 (16.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Filter paper, however, inhibits ITS-PCR, making it less accurate compared to when DNA is extracted directly from whole blood samples (Ahmed et al, 2013 ). The frequency in trypanosome species, T. congolense and T. vivax distribution were similar with other findings (Kebede et al, 2009 ; Von Wissmann et al, 2011 ; Maganga et al, 2020 ), where goats were found to be highly prevalent in T. vivax as compared to cattle which is highly prevalent in T. congolense (Hassan-Kadle et al, 2020 ; Mulenga et al, 2021 ). In livestock, T. congolense and T. vivax are the most prevalent under natural infections, while T. brucei is the least prevalent (Van den Bossche and Delespaux, 2011 ; Maganga et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Filter paper, however, inhibits ITS-PCR, making it less accurate compared to when DNA is extracted directly from whole blood samples (Ahmed et al, 2013 ). The frequency in trypanosome species, T. congolense and T. vivax distribution were similar with other findings (Kebede et al, 2009 ; Von Wissmann et al, 2011 ; Maganga et al, 2020 ), where goats were found to be highly prevalent in T. vivax as compared to cattle which is highly prevalent in T. congolense (Hassan-Kadle et al, 2020 ; Mulenga et al, 2021 ). In livestock, T. congolense and T. vivax are the most prevalent under natural infections, while T. brucei is the least prevalent (Van den Bossche and Delespaux, 2011 ; Maganga et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…Despite our study reporting no cases of T. brucei from the goats sampled, indicating that T. brucei was not circulating in the goats sampled. Our findings were consistent with observations made by Kebede et al ( 2009 ) and Van den Bossche et al ( 2010 ), but disagreed with findings from other studies where T. brucei was found to be highly prevalent (Von Wissmann et al, 2011 ; Hassan-Kadle et al, 2020 ). The absence of T. brucei in our study may have been attributed to the inability of the sample collection technique i.e., filter paper, to preserve enough DNA to be detected by PCR.…”
Section: Resultssupporting
confidence: 84%
“…In parallel, multiple meetings and webinars have been organized to raise awareness about the importance of OH in the country. Our research efforts have resulted in several notable scientific publications on zoonotic diseases, including the first molecular investigations of animal trypanosomiasis in Somalia [ 19 , 20 ]. Data provided by our studies on brucellosis and toxoplasmosis in pregnant women emphasized the significance of understanding zoonotic abortifacient pathogens in the Somali community [ 21 ].…”
Section: Status Of Oh In Somaliamentioning
confidence: 99%
“…The prevalence of zoonotic diseases such as brucellosis, Rift Valley fever (RVF), Q fever, and toxoplasmosis is a pressing concern in Somalia, contributing significantly to public health risks and economic burdens (Frangoulidis et al., 2021; Hassan‐Kadle et al., 2019, 2020, 2021; Yusuf et al., 2021). However, to the best of our knowledge, the presence of Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%